O espaço e a infância das crianças de 0 a 4 anos que não freqüentam a educação infantil em Vitória da Conquista - Araujo, Ana Lucia Castilhano de (2008)
This research talks about children without childhood care assistence. The investigation was made about children between zero and four years old, in a location in the city of Vitória da Conquista, state of Bahia, Brazil. The task of do an aproaching with children who lives in a knowledge and public politics border sends this research to an non explored field os families homes with small children. After an aproaching process and contacts with the comunity for localize children without of pré-schools or childhood care centers, observations were developed about children and their families including the comunity around them emphasizing space as a socializing element and made by adult and children as well. The context of small children without childcare shows a familiar and spacial structure of control and reclusion that can be explained by their age such as cultural causes. The research used photograph to show children space. Some of them taking by the children themselves. The discussion presented try to show the ways that children can live their childhoods using their reality, space, family, objects, experiencing with adults conflict relatinships but always in a constant interaction.